A High Resolution Radiation Hybrid Map of Wheat Chromosome 4A - Balcárková, Barbora; Frenkel, Zeev; Škopová, Monika; Abrouk, Michael; Kumar, Ajay; Chao, Shiaoman; Kianian, Shahryar F.; Akhunov, Eduard; Korol, Abraham B.; Doležel, Jaroslav; Valárik, Miroslav (Frontiers in Plant Science, 2017)
Bread wheat has a large and complex allohexaploid genome with low recombination level at chromosome centromeric and peri-centromeric regions. This significantly ham-pers ordering of markers, contigs of physical maps and sequence scaffolds and impedes obtaining of high-quality reference genome sequence. Here we report on the construc-tion of high-density and high-resolution radiation hybrid (RH) map of chromosome 4A supported by high-density chromosome deletion map. A total of 119 endosperm-based RH lines of two RH panels and 15 chromosome deletion bin lines were genotyped with 90K iSelect SNP array. A total of 2316 and 2695 markers were successfully mapped to the 4A RH and deletion maps, respectively. The chromosome deletion map was ordered in 19 bins and allowed precise identification of centromeric region and verification of the RH panel reliability. The 4A-specific RH map comprises 1080 mapping bins and spans 6550.9 cR with a resolution of 0.13 Mb/cR. Significantly higher mapping resolu-tion in the centromeric region was observed as compared to recombination maps. Rela-tively even distribution of deletion frequency along the chromosome in the RH panel was observed and putative functional centromere was delimited within a region charac-terized by two SNP markers.